Assessing interpersonal trust in an ambient intelligence negotiation system - Gomes, Marco Filipe Vieira (2016)
This paper describes an approach to assess and measure trust based on a specific Ambient Intelligence environment. The primary aim of this work is to address and expand on this line of research by investigating the possibility of measuring trust based on quantifiable behavior. To do so, we present a brief review of the existing definitions of trust and define trust in the context of an Ambient Intelligence (AmI) scenario. Further, we propose a formal definition so that the analysis of trust in this kind of scenarios can be developed. Thus, it is suggested the use of Ambient Intelligence techniques that use a trust data model to collect and evaluate relevant information based on the assumption that observable trust between two entities (parties) results in certain typical behaviors. This will establish the foundation for the prediction of such aspects based on the analysis of people’s interaction with technological environments, providing new potentially interesting trust assessment tools.